Parasitic load and self-medication of Bornean Orangutan (Pongo pygmaeus ssp. wurmbii) in Sebangau National Park Central Kalimantan Indonesia. Issue 1 (April 2021) - Panda, A; Djohan, T S; Artama, W T; Priyowidodo, D
Abstract: Around 27.5% of human parasites have been found in primates. It is proposed that this parasitic load prevalence is not reflected in the specificity of the host or hosts capable of battling parasite infection. Since the dynamic of the field contributes to a broader understanding of host-parasite relationships, it is critical to proving what hosts capable of, in the first place. Therefore, the purpose of the study was to present adequate evidence of the Orangutan's capacity to medicate itself. In September – October 2017, a swift assessment was carried out in the Punggualas area, Sebangau National Park (SNP). As per behavior procedure, a total of 72 hours follows on habitual Orangutan, on which focal behaviors, including their social behavior, have been reported every 2 minutes. All data is evaluated descriptively. Three focal orangutans, consisting of two dominant males, namely Eboy and Sander, and one independent female with an infant. The results showed that two male individuals revealed no signs of self-medication activity in their natural diets, only feeding activity. In the meanwhile, the female shows the actions. While we did not specifically find out the symptom they may have, the research outcome gained ample evidence that self-medication is performed by the Orangutan.